(NpOWESTI(B; (NsTATXI(B; (No^ERKI (B/s (N~ASTX (B4s - (NpASTERNAK(B, (NbORIS lEONIDOWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1991)
(Nw TOM WKL@^ENY POWESTI (B("(NdETSTWO l@WERS(B", "(NwOZDU[NYE PUTI(B", "(Nl@DI I POLOVENIQ(B" (NI DR(B. ), (NSTATXI(B, (NDRAMATI^ESKIE PROIZWEDENIQ(B, (NWYSTUPLENIQ(B, (NZAMETKI I NEOKON^ENNAQ PROZA bORISA pASTERNAKA(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs